2018
DOI: 10.3390/ani8110195
|View full text |Cite
|
Sign up to set email alerts
|

Use of Foaming Disinfectants and Cleaners to Reduce Aerobic Bacteria and Salmonella on Poultry Transport Coops

Abstract: Simple SummaryChicken coops are rarely washed and can soil poultry carcasses with fecal bacteria that may make people sick. Our laboratory applied two commercially available products to experimentally contaminated coops. One product contained bleach, potassium hydroxide and a foaming agent. The other product contained vinegar and hydrogen peroxide and was mixed with a detergent. Both products were applied using a firefighting apparatus known as a compressed air foam system (CAFS). These materials were washed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
4
8
0
Order By: Relevance
“…Furthermore, individual measures such as adding detergent or disinfectant or raising the temperature of the wash water did not, by themselves, result in a significant reduction in microbial counts. Recently, other authors have shown that using compressed air foam systems with a cleaner (peracetic acid or chlorinated) may be used to successfully reduce aerobic bacteria in poultry transport crates (Hinojosa et al , ). However, on those studies, the crates were artificially contaminated and the efficacy of the cleaning methods in reducing viral contamination was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individual measures such as adding detergent or disinfectant or raising the temperature of the wash water did not, by themselves, result in a significant reduction in microbial counts. Recently, other authors have shown that using compressed air foam systems with a cleaner (peracetic acid or chlorinated) may be used to successfully reduce aerobic bacteria in poultry transport crates (Hinojosa et al , ). However, on those studies, the crates were artificially contaminated and the efficacy of the cleaning methods in reducing viral contamination was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…[15-34, 35•, 36-38] and Salmonella spp. [15,19,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] were carried out in thirteen and eleven different countries, respectively. For both pathogens, most of the pre-harvest interventions were assessed in lab-based challenge trials (65% and 82%), while the remaining trials were field trials where no experimental infection was performed.…”
Section: Resultsmentioning
confidence: 99%
“…For E. coli , the effect of the sanitation procedure depended on the sampling point, in that compared with presanitation samples collected from dry-cleaned barns, the E. coli concentration was lower in postsanitation samples collected from disinfected barns. Davies and Wray (1995) showed that S. enterica and coliform populations increase during the pressure washing process often used before disinfection, whereas others have shown that using a high-pressure rinse before disinfection was more effective against E. coli ( Berrang and Northcutt, 2005 ) and S. enterica ( Hinojosa et al., 2018 ) than a low-pressure rinse. Gibson et al.…”
Section: Discussionmentioning
confidence: 99%